Mathematical modeling of quartz particle melting process in plasma-chemical reactor; AIP Conference Proceedings; Vol. 1698 : Advanced materials in technology and construction: AMTC-2015 - Volokitin O. G. Oleg Gennadjevich; Vlasov V. A. Viktor Alekseevich; Volokitin G. G. Gennady Georgievich; Skripnikova N. K. Nelli Karpovna; Shekhovtsov V. V. Valentin Valerjevich (2016, 2016)
Title screen